Epistemología histórica y las ciencias sociales - Rivera Palomino, Juan (2008)
On basis of the new knowledge of the astrophysical teories the fractal geometry and the scientific practice one can sustain the historical epistemology, relieving the heuristical and the change and the historical devolepment of the science and the tecnology. This kind of development is n ot continuos, lineal and secuencial. Against what statement the sistemicals, the hermenustics and the post modern. In this paper I exponse and explain the main onthologicals, gnoseologicals and epistemologicals thesis. Which groundwork it and the main cathegorys that propose to study the social reality from and historical rationality against of the logicist reductionism of the neopositivism.